Monetary policy uncertainty and monetary policy surprises. (April 2021) - De Pooter, Michiel; Favara, Giovanni; Modugno, Michele; Wu, Jason
Abstract: Monetary policy uncertainty affects the transmission of monetary policy shocks to longer-term nominal and real yields. For a given monetary policy shock, the reaction of yields is more pronounced when the level of monetary policy uncertainty is low. Primary dealers and other investors adjust their interest rate positions more when monetary policy uncertainty is low than when uncertainty is high. These portfolio adjustments likely explain the larger pass-through of a monetary policy shock to bond yields when uncertainty is low. These findings shed new light on the role that monetary policy uncertainty plays in the transmission of monetary policy to financial markets.